Practical activities in mathematics teaching – mathematics teachers’ knowledge based reasons - Haara, Frode Olav; Smith, Kari (NOMAD Nordic Studies in Mathematics Education, 2009)
The current article assumes that mathematics teachers’ understanding of mathematics and professional beliefs are integrated into their professional knowledge. The focus of the article is on teachers’ knowledge based explanations and reasons for choosing practical activities in the teaching of mathematics. Based on interviews of eight mathematics teachers in Norwegian elementary school (where the pupils are 6 to 16 years old), the article analyses and discusses relations between mathematics teachers’ professional knowledge and choice of using practical activities. The findings give grounds for suggesting that both disciplinary and didactical knowledge have an impact on teachers’ choice, and that inexperienced teachers do not have clear knowledge based explanations or reasons for using practical activities at the level of experienced teachers. However, the inexperienced, yet acknowledged teacher will, regardless of high or minimal disciplinary knowledge in mathematics, develop a more thorough and clear opinion on about practical activities as the pedagogical content knowledge deepens through experience.